ANALISIS STRATEGI PENGEMBANGAN BISNIS ALEN – ALEN MBAK SRIPIT MELALUI BUSINESS MODEL CANVAS - Putri, Sherly Yulia; Kusumaningtyas, Dian; Damayanti, Susi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
UMKMs in Trenggalek Regency are developing very rapidly. However, Alen-alen Mbak Sripit's business is still not widely known in the consumer market. So it hasn't developed much like other home industry businesses. This research aims to find out the analysis of the business strategy "Alen-alen Mbak Sripit" through the Business Model Canvas. Researchers used a qualitative approach with descriptive methods. The object of the research is devoted to UMKM Alen-alen Mbak Sripit in Pojok Village, Pogalan sub-district, Trenggalek Regency. Data collection procedures, namely observation, interviews, and documentation. Data analysis techniques are using data reduction, data presentation, drawing conclusions, and the SWOT matrix. The results of data analysis using the Business Model Canvas on Mbak Sripit's Alen-alen business show that there are things that need to be added to the customer segment, namely expanding customer targets by identifying new customer segments. Value proposition by adding marketing channels such as Shopee, TikTok, and Tokopedia. The facilities that need to be improved are customer relationships, the development of key resources, and key partnerships that are professionals in their fields in order to minimize operational costs.